PROBLEM OF LAND OWNERSHIP CERTIFICATES AS LEGAL PROOF OF OWNERSHIP - Frina Debora; Icha Jesika Manalu; Muhajir Muhajir; Pasquale Roy Bagaskara; Rodia Musdalifah Tiofan; Samuel Febrian (Problematika Hukum, 2022)
Agrarian is the natural resource that humans need most, as a place to live and develop land resources. This development aims to achieve shared prosperity. maintain collective order and guarantee every community's rights in every region. So it is necessary to regulate in law a policy that determines land ownership according to the rights of each individual. Because if it is not regulated it will cause problems in social life. Because of this, the government passed legislation regulating the significance of land ownership as attested to by a Certificate of Ownership or Letter of Ownership (SHM). The government hopes that with SHM, every person who owns land or buildings (certain objects) can have their ownership rights guaranteed in compliance with relevant laws and regulations. Thus, if there is a struggle for property rights, it can be proven by the existence of SHM. Based on Law No. 5 of 1960 and Government Regulation No. 24 of 1997 emphasizes the crucial role of land ownership certificates as legal proof of ownership. This contributes to legal certainty, protection, and justice in the context of land ownership and transactions.Keywords: Problematic, Freehold Title, Land, Evidence, Ownership, Legal.